2005
DOI: 10.1111/j.1600-0749.2005.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemocyanin in the exoskeleton of crustaceans: enzymatic properties and immunolocalization

Abstract: We investigated the enzymatic properties and immunohistochemical localization of cuticular hemocyanin, a known oxygen transporter in the prawn Penaeus japonicus. The molecular weight of hemocyanin purified from the cuticle was estimated to be 67-77 k using SDS-PAGE, and the purified protein was effectively converted into a phenoloxidase-like enzyme by an SDS-treatment. The activated enzyme catalyzed the o-hydroxylation of monophenols and the oxidation of o-diphenols and was inhibited by typical inhibitors of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 23 publications
5
50
0
Order By: Relevance
“…The arthropod cuticle was considered traditionally to be an inert supporting exoskeleton, a protective barrier against microorganisms and an exchange surface (Adachi et al 2005). However, recent evidence suggests that the arthropod cuticle also contributes to various biochemical and physiological processes ( Willis 1999;Willis et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The arthropod cuticle was considered traditionally to be an inert supporting exoskeleton, a protective barrier against microorganisms and an exchange surface (Adachi et al 2005). However, recent evidence suggests that the arthropod cuticle also contributes to various biochemical and physiological processes ( Willis 1999;Willis et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Arthropod cuticle is not solely a physical barrier to the environment but can contribute to critical processes such as immune responses and cross-linking for cuticle hardening and calcification of exoskeleton (Ashida and Brey, 1995;Sugumaran and Nelson, 1998;Adachi et al, 2005;Suderman et al, 2006;Glazer et al, 2013). In crustaceans, cuticle tearing leaks hemolymph and releases proteins, which coagulate sealing the wound and preventing infection (Iwanaga et al, 1998;Li et al, 2002;Jiravanichpaisal et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Hemocyanin can also be converted into phenoloxidase (Adachi et al, 2005;Adachi et al, 2001;Decker and Jaenicke, 2004). In addition, Adachi and colleagues (Adachi et al, 2005) identified hemocyanins in the cuticle of the shrimp Penaeus japonicus, and demonstrated the in vitro phenoloxidase activity of the enzyme. These authors further suggested that cuticular hemocyanin functions as a sclerotizing agent and/or an innate immunity factor.…”
Section: Introductionmentioning
confidence: 99%
“…These precursors are secreted into the hemolymph, where they can be activated by specific proteinases or can be deposited in the cuticle, where they are activated on site (Söderhäll and Cerenius, 1998). Crustacean hemocyanins are expressed in the hepatopancreas of several species (Adachi et al, 2005;Durstewitz and Terwilliger, 1997;van Holde and Miller, 1995) and are secreted to the hemolymph, where they occur as large extracellular multi-subunit molecules (van Holde and Miller, 1995). Hemocyanin can also be converted into phenoloxidase (Adachi et al, 2005;Adachi et al, 2001;Decker and Jaenicke, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation